Mineral Content in Dehydrated Mango Powder - Mujahid Hussain Leghari,; Saghir Ahmed Sheikh,; M.B. Kumbhar,; A.F. Baloch, (Journal of Basic & Applied Sciences, 2021)
The study was carried out to explore mineral content in dehydrated mango powder made from immature green stage fruits. For the purpose, two type of slices from peeled and unpeeled fruits of four commercial grown varieties viz. Desi, Sindhri, Langra and Chaunsa were prepared. These slices were categorized into three groups A, B and C. In group A, slices were kept in controlled conditions in electric cabinet chamber (dehydrator) at 65oC temperature, while in group B, slices were dried by open sun drying method using muslin cloth over the cots at (43 ± 5 oC) and in group C, slices were kept in wooden glass dehydrator at (48 ± 4 oC). The statistical analysis reveals highly significant differences for all main factors including varieties, dehydration methods, type of mango powder and their interactions. Chaunsa had the highest mean calcium (389.54 mg kg-1), potassium (912.07 mg kg-1) and magnesium (90.92 mg kg-1). However, only sodium was observed more in variety Langra (467.59 mg kg-1). On the basis of dehydration methods, mean calcium (407.06 mg kg-1) and magnesium (90.11 mg kg-1) content were observed more in wooden glass drying method as compared to rest of the drying methods. The sodium (511.83 mg kg-1) and potassium (811.35 mg kg-1)content were recorded the highest in open sun drying method. The powder made from fruits without peel was observed more in all mineral content including sodium, calcium, potassium and magnesium.